Penerapan Hukum Terhadap Tindak Pidana Pembunuhan Dengan SengajaMerampas Nyawa Orang Lain(Studi Kasus Nomor Putusan 616/Pid.B/2015/PN. Lbp) - Dimo Maulid (Yayasan Lentera Keadilan Cendikia, 2025)
It is a fact that in human social life, both individuals and groups, there are often deviations from social norms, especially known as legal standards. Deviations from these legal standards are referred to as criminal acts in the general public. Crimes against human souls have increased in society in recent years. This study uses library and field research. The judge's consideration, also known as the ratio decidendi, is an argument or reason used by the judge as a basis for making a decision on a case. Before proving this legal consideration, the judge first collects the facts of the trial, which include conclusions from witnesses, defendants, and evidence.